CNTN-1 Upregulation Induced by Low-Dose Cisplatin Promotes Malignant Progression of Lung Adenocarcinoma Cells via Activation of Epithelial-Mesenchymal Transition - Zhang, Ruijie; Li, Shengjin; Lan, Jian; Li, Changyi; Du, Xianzhi; Dong, Weijie; Yu, Qian; Wang, Daoxin (Frontiers in Genetics, 2022)
Tumor metastasis and invasion are the main impediments of lung adenocarcinoma successful treatment. Previous studies demonstrate that chemotherapeutic agents can elevate malignancy of cancer cells other than their therapeutic effects. In this study, the effects of transient low-dose cisplatin treatment on the malignant development of lung adenocarcinoma cells (A549) were detected, and the underlying epigenetic mechanisms were investigated. The findings showed that A549 cells exhibited epithelial-mesenchymal transition (EMT)-like phenotype along with malignant progression under the transient low-dose cisplatin treatment. Meanwhile, low-dose cisplatin was found to induce contactin-1 (CNTN-1) upregulation in A549 cells. Subsequently, we found that further overexpressing CNTN-1 in A549 cells obviously activated EMT process in vitro and in vivo, and caused malignant development of A549 cells in vitro. Taken together, we conclude that low-dose cisplatin can activate EMT process and resulting malignant progression through upregulating CNTN-1 in A549 cells. The findings provided new evidences that low concentration of chemotherapeutic agents could facilitate malignancy of carcinoma cells via activating EMT process other than their therapeutic effects.